Delopment and Validation of a Self-Efficacy Scale for Distance Learning - Gede Suwardika; Agus Tatang Sopandi; Indrawan, Putu Oktap (LPPM Undiksha, 2024)
Not all students are ready to face changes, primarily related to self-efficacy in the context of entirely technology-based learning. This study aims to develop and validate a reliable and valid Self-Efficacy Scale for Distance Learning/SESDL. This scale is designed to measure self-efficacy in students studying in the context of distance learning. This study involved 151 UPBJJ-UT Denpasar students selected using Cluster Sampling. The instrument developed consisted of 34 statement items covering three dimensions of self-efficacy, namely magnitude, strength, and generality. Validation was done through confirmatory factor analysis (CFA) and the Rasch model. The analysis showed that the SESDL instrument had high reliability, strong construct validity, and good model fit. Educators, researchers, and practitioners can use this scale to accurately measure student self-efficacy in distance learning. The implications of this study are that it significantly impacts various parties in the world of education. For educators and educational institutions, this scale can be used as an evaluation tool to understand student self-efficacy in the context of distance learning. With this understanding, educators can design more targeted strategies and methods to increase students' self-confidence in overcoming the challenges of distance learning, such as improving time management skills, learning independence, and using technology.